2006
DOI: 10.1007/s10397-006-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex hyperplastic endometrium in a peritoneal leiomyoma following a CISH hysterectomy

Abstract: We describe a case of a patient presenting with an abdominal tumor 4 years after a classical intrafascial serrated-edged macro-morcellated hysterectomy. The tumor was removed surgically and proved microscopically to be a peritoneal leiomyoma containing complex hyperplastic endometria. To our knowledge, this has never been described before. In addition, the pathogenesis of this rare disease is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Summarising the case reports and series, a total of 69 women with parasitic myoma after laparoscopic morcellation were identified. Data of all case reports and series are presented in the Supplementary material (Table S1) . The mean age at diagnosis was 40.8 (± 7.5) years (range 24–57) and the majority of the women were premenopausal ( n = 59; 85.5%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summarising the case reports and series, a total of 69 women with parasitic myoma after laparoscopic morcellation were identified. Data of all case reports and series are presented in the Supplementary material (Table S1) . The mean age at diagnosis was 40.8 (± 7.5) years (range 24–57) and the majority of the women were premenopausal ( n = 59; 85.5%).…”
Section: Resultsmentioning
confidence: 99%
“…One woman underwent a unilateral oophorectomy at the time of morcellation . Eight women (11.6%) received hormonal replacement therapy before the diagnosis of a parasitic myoma . Five of these women had undergone a BSO and three women received hormonal replacement therapy for reasons not clearly stated in the case reports .…”
Section: Resultsmentioning
confidence: 99%
“…The authors do not report conflict of interest Abdel-Gadir, 2010 75 Al Manasra, 2011 59 Al Talib, 2010 9 Al Talib, 2010 9 Atkin, 2010 110 Aust, 2011 58 Berhan, 2003 56 Boqusiewicz, 2013 65 Brieger, 1995 40 Brody, 1953 93 Chan, 2004 12 Chu, 2012 86 Cucinella, 2011 36 Dan, 2012 52 Donnez, 2007 38 Elagwany, 2014 92 Epstein, 2009 94 Florez-Peña, 2012 87 Ghamande, 1996 57 Giannelli, 2013 83 Gómez, 2014 106 Goppel, 2009 68 Green, 2011 95 Hartzell, 2014 39 Hayashi, 2015 44 Heinig, 2003 24 Heuer, 2013 66 Hilger, 2006 23 Hirayama, 2015 42 Holloran, 2015 51 Huang, 2014 19 Hwang, 2010 60 Jebunnaher, 2013 73 Kamaci, 2004 118 Kang, 2009 76 Karadza, 2013 46 Kawasaki,2013 43 Kebapci, 2002 55 Keogh, 2003 84 Kill, 2011 48 Kho, 2009 3 Knudsen, 2006 49 Kumar, 2008 63 LaCoursiere,2005 116 Larrain, 2010 136 Lee, 2012 …”
Section: Conflict Of Interestmentioning
confidence: 98%
“…Sometimes parasitic leiomyomas are associated with other benign conditions such as endometrial cysts 46 or endometriosis 47 and can even undergo atypical transformation 48,49 .…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
“…6 It is suggested that the term "postsupracervical hysterectomy syndrome" be used for patients presenting with symptomatology following supracervical hysterectomy due to peritoneal implantation of myometrial or endometrial morsels occurring at the time of uterine morcellation or due to the retained cervical stump.…”
Section: Commentmentioning
confidence: 99%